The Effectiveness of Augmented Reality with Adapted Books as Emotional Expression Media for Children with Autistic Spectrum Disorders (ASD) - Tolle, Herman; Nerea López, Jonathan del Moral (Universitas Dharma Wacana, 2024)
Autism Spectrum Disorder (ASD) is a neurological condition that affects a person's ability to recognize and understand emotions, thereby hindering social interactions. This research introduces AREmotion, an augmented reality (AR) mobile application integrated with an adapted book, designed to aid children with ASD in recognizing emotional expressions. Using images as markers in the AR application, AREmotion facilitates the learning process for these children. The study employed a pre-experimental design with a one-group pre-test and post-test to evaluate the application's effectiveness. Results indicated a significant improvement in the participant's ability to understand emotional expressions, with each respondent showing a significance value of less than 0.05. These findings demonstrate that combining AR technology with traditional printed books can effectively enhance emotional recognition in children with ASD, showcasing a promising advancement in this field.